மங்கையின் பனித்தீ - மீள்புனைவாக்கமும் நவீன நாடகப்பனுவலாக்கமும் / Mangai’s Paniththee – Re-reading and Modern Drama Textualization - ச. ஹேம பூஜா/S. Hema Pooja; முனைவர் இரா. மணிக்கண்ணன்/Dr R. Manikannan (International Journal of Tamil Language and Literary Studies, 2021)
The theoretical thinking of feminism has had a tremendous impact on various spheres of human life. Feminist ideology stands for the fact that all fields such as history, myth, and culture, need to be re-read. Feminist readings on myths continue to emerge in various levels. In addition to this, in the ‘Mahabharata’, the author of the Ambai myth, A. Mangai has been transformed into a modern drama by the name of ‘Paniththee’. The play explores the openness with which the play criticizes the ‘Mahabharata’ and the feminist voice of the copy within the transformation and the system in which the text is based on concepts such as the critique of male domination, the seizure of power, the autonomy of woman, and the parody of male fiction.